2020
DOI: 10.3386/w27028
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Fraction of Unreported Infections in Epidemics with a Known Epicenter: an Application to COVID-19

Abstract: for their helpful comments. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Second, we target the fraction of undetected infections from the estimates in Stock et al (2020), who use results from Iceland's two testing programs and estimate that the fraction of undetected infections range from 88.7% to 93.6%. We target a fraction of 90% undetected infections, which are also consistent with the estimates for the US in Hortaçsu et al (2020). The calibrated values of β and d I are 0.1504 and 0.0163, respectively; we show sensitivity analysis to these values below.…”
Section: Calibrationsupporting
confidence: 57%
“…Second, we target the fraction of undetected infections from the estimates in Stock et al (2020), who use results from Iceland's two testing programs and estimate that the fraction of undetected infections range from 88.7% to 93.6%. We target a fraction of 90% undetected infections, which are also consistent with the estimates for the US in Hortaçsu et al (2020). The calibrated values of β and d I are 0.1504 and 0.0163, respectively; we show sensitivity analysis to these values below.…”
Section: Calibrationsupporting
confidence: 57%
“…We note that while the average medical duration from the onset of symptoms to death for COVID-19 is longer than two weeks (around 18 days, see Verity et al, 2020), the duration from reported cases to deaths is likely to substantially shorter because of reporting delays. For example, Hortaçsu, Liu and Schwieg (2020) assume that new cases of COVID-19 are reported with a lag of 8 days in their baseline calculations (5 days for symptoms to appear, consistent with the evidence from Lauer et al (2020) and Park et al (2020), as people are unlikely to be tested without exhibiting symptoms, and an additional 3 days to capture delays in obtaining test results, based on andecdotal reports from the US). Since deaths are likely reported in a timely manner, if new cases are reported with a lag of 8 days, we would expect an average duration of around 10 days (≈1.43 weeks) between reported cases and reported deaths. As a second validation check, we ask whether our estimates of ℛ t are correlated with past movement data, as it should be if the estimates are meaningful.…”
Section: Sis Modelmentioning
confidence: 99%
“…On the other hand, the peak value of the traditional model is much higher than the reported data. Although the number of actual cases is considered higher than the number of reported cases ( Calafiore et al, 2020 ; Hortaçsu et al, 2020 ; Liu et al, 2020 ), the epidemic development trend simulated by the Statistical-SIR model is basically in line with the facts, which can provide a reference for policymakers and medical resource allocation. In fact, limited by medical conditions and testing levels, the reported number of newly confirmed daily cases in India and Brazil cannot reach 200 000 and 300 000, respectively.…”
Section: Results and Analysismentioning
confidence: 95%